Pemetaan Tingkat Kerapatan Vegetasi di Kota Palu Menggunakan Citra Sentinel 2A - Suni, Muhammad Adam; Fitra, Ramad Arya; Masserang, Busranuddin Daeng; Pritta, Birgitta Karlina (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The background for making this map in community service is the need for data on the area of vegetated areas and the level of vegetation density by various parties, both from government agencies, research and education needs, and non-government agencies. Meanwhile regional development and increase in residential land are increasing from year to year. To find out the area of vegetated areas and the level of density of vegetation effectively and efficiently, mapping can be done using remote sensing. The purpose of this community service is to find out the area of vegetated areas and the level of vegetation density in Palu City in 2022. This community service is a descriptive research. The area of the vegetated area and the level of vegetation density were obtained through remote sensing using the Normalized Difference Vegetation Index (NDVI) method utilizing Sentinel 2-A imagery and direct field surveys. The result of this community service is a map of the level of vegetation density in the city of Palu in 2022, which shows that there are 4 (four) classes of vegetation density, namely the non-vegetation class of 3,602.77 Ha. Rare vegetation class 3,649.22 Ha. Medium vegetation class 6,539.65 Ha. Dense vegetation class 24,175.91 Ha